Comparative Analysis of the Age, Gender, and Ferritin Levels with Hepcidin in Iraqi Patients Suffering Beta Thalassemia (Major and Intermedia) - A. Al-Husseiny, Istabraq; Al-Jumaili, Essam F. (Bogor Agricultural University, Indonesia, 2025)
Beta thalassemia is a hereditary, autosomal recessive blood condition. The present investigation aims to assess the relationship between ferritin and hepcidin serum levels, age, and gender in patients with β-thalassemia major (βTM) and β-thalassemia intermedia (βTI). Two groups of 100 patients, including 39 females and 61 males, were identified: 73 patients had (βTM), and 27 had range spans. The age range spans from 1 to 46 years. The patients were registered at the Al-Krama Teaching Hospital, Hereditary Blood Disorder Center, Baghdad, between June 2023 and April 2024. The study's control group consisted of 50 healthy individuals in similar age groups. Human ELISA kits were used to measure the amounts of serum ferritin and hepcidin. The mean age of the βTM and βTI patients differed significantly from that of the control groups (p-value 0.001). Gender-wise, males were more affected than females in the βTM and βTI groups. The Hb concentration was much lower in the patient's blood samples. The Ferritin with hepcidin concentrations in the serum of βTM and βTI showed a significant difference at the 0.001 level. The control had the lowest value. The current study's findings demonstrated elevated blood levels of hepcidin and Ferritin in the βTM and βTI groups, with the βTI group showing noticeably higher levels.